DESIGN OF A VERTICAL ANNULUS WITH MHD FLOW USING ENTROPY GENERATION ANALYSIS - Mahian, Omid; Öztop, Hakan Fehmi; Pop, Ioan; Mahmud, Shohel; Wongwises, Somchai (Vinca Inst Nuclear Sci, 2013)
Optimal design of a heat exchanger is one of the concerns of energy conversion engineers. In the present work, the mixed convection flow between two vertical concentric pipes with constant heatflux at the boundaries and MHD flow effects is considered. To determine the optimal design for such a heat exchanger, at first, the momentum and energy equations are simplified and solved analytically. Next, using entropy generation analysis and cost analysis, the operational costs due to entropy generation are estimated. It is concluded that with an increase in the Hartmann number, the energy costs increase. In addition, for two small deviations from the base radius ratio (Pi = 2) including Pi = 19 and Pi = 2.1, the changes in the energy cost are calculated. It is found that for Pi = 1.9 the energy cost increases by 17.5% while for Pi = 2.1 the energy cost is reduced by 13.6%.
Keywords: vertical annulus; magnetic field; mixed convection; entropy generation; cost analysis